2000
DOI: 10.1136/thorax.55.5.370
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 expression in sputum eosinophils in patients with acute asthma

Abstract: Background-Eosinophils play a pivotal role in asthmatic airway inflammation. Apoptosis is thought to be critically relevant in promoting the clearance of inflammatory cells and the resolution of inflammation. Bcl-2 inhibits apoptosis in cellular systems. A study was undertaken to determine whether bcl-2 expression in sputum reflects the clinical severity of patients with asthma. The relationship between bcl-2 expression in sputum eosinophils and eosinophil activation markers such as interleukin (IL)-5 and eosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 17 publications
5
18
0
Order By: Relevance
“…Fas expression on eosinophils of healthy and asthmatic subjects appears similar [112], but studies of patients with ragweed-allergic asthma have demonstrated increased concentrations of TRAIL 24 h after allergen challenge in asthmatic subjects as compared with controls, which correlates with airway eosinophilia [113]. There is evidence of increased expression of the anti-apoptotic protein Bcl-2 in eosinophils from sputum of patients with severe asthma [114]. Eosinophil apoptosis regulates clearance of these cells from the airway; BECs (bronchial epithelial cells) phagocytose apoptotic eosinophils [115] and treatment with glucocorticoids increases the clearance of these cells by both BECs and alveolar macrophages [113].…”
Section: Eosinophil Apoptosis In Allergic Inflammationmentioning
confidence: 97%
“…Fas expression on eosinophils of healthy and asthmatic subjects appears similar [112], but studies of patients with ragweed-allergic asthma have demonstrated increased concentrations of TRAIL 24 h after allergen challenge in asthmatic subjects as compared with controls, which correlates with airway eosinophilia [113]. There is evidence of increased expression of the anti-apoptotic protein Bcl-2 in eosinophils from sputum of patients with severe asthma [114]. Eosinophil apoptosis regulates clearance of these cells from the airway; BECs (bronchial epithelial cells) phagocytose apoptotic eosinophils [115] and treatment with glucocorticoids increases the clearance of these cells by both BECs and alveolar macrophages [113].…”
Section: Eosinophil Apoptosis In Allergic Inflammationmentioning
confidence: 97%
“…Previous reports investigating the role of Bcl-2 homologues in eosinophils have concentrated on the level of protein expression. Human peripheral blood eosinophils endogenously express relatively high levels of proapoptotic Bax and antiapoptotic Bcl-x L , with little or no detectable antiapoptotic Bcl-2 expression, 12,13 although there is some evidence of higher Bcl-2 expression in eosinophils derived from patients with asthma and hypereosinophilic syndrome, 14,15 and stimulation in vitro with IL-5 resulted in detectable up-regulation of Bcl-2 expression in some 12,16 but not all studies. 17,18 It has been proposed that susceptibility to cell death is determined by the ratio of death agonist to death antagonist and their subsequent interactions by homodimerization and heterodimerization, via conserved BH3 domains.…”
mentioning
confidence: 99%
“…On the one hand, inflammatory cells, especially eosinophils, are known to play an important role in the onset and maintenance of asthma (Vignola et al, 1999;Druilhe et al, 2000), while the inhibition of inflammatory cell apoptosis in acute asthma is associated with the expression of pro-and antiapoptotic genes (Jang et al, 2000). bcl-2 is a type of apoptosis suppression gene, while bax or p53 are examples of proapoptotic genes.…”
Section: Discussionmentioning
confidence: 98%
“…It also could increase asthma morbidity and aggravate asthma symptoms by enhancing the sensitivity of asthma patients to antigen (Grella et al, 2002). Although the pathogenesis of asthma is still not clear, inhibition of cell apoptosis might play an important role in the development of asthma (Jang et al, 2000).…”
Section: Introductionmentioning
confidence: 99%